High Resolution Electron Microscopy and X-Ray Study of Cancrinite - Hassan, Ishmael (My University, 1980)
High resolution electron microscopy has provided information on the submicroscopic structure of a (Na, Ca) CO₃ cancrinite from Ontario and this information assisted in re-fining the average crystal structure (R=2.9%) by standard X-ray techniques.
The superstructure of this mineral is commensurate and superlattice reflections can be indexed on a 8c₀ - supercell. Six out of the seven such reflections have been observed by the electron and x-ray diffractions. It is shown that the ordering of the CO₃ ions in the large channels is responsible for the superlattice reflections.
Furthermore, 'cancrinites' reported in the literature show superstructures that can be indexed on supercells of 5c₀, 7c₀, 8c₀, 11c₀, 14c₀ and 16c₀. The ordering of the CO3 ions is again responsible for these extra reflections.
Moreover, the framework structures of three new mineral phases (liottite, afghanite and franzinite) that have recently been discovered are the same as that of cancrinite. They differ only as regards the intraframework anions (SO₄, CO₃ and Cl). The chlorine is statistically distributed with H₂O in the cages and the ordering of the SO₄ and CO₃ in the large channels gives rise to commensurate superstructure reflections which can be indexed on multiple subcells i.e., 3c₀, 4c₀, and 5c₀ for liottite, afghanite and franzinite respectively.
In addition, losod and microsommite (or davyne) also fit within the framework of the proposed model. Losod can be considered as 2c₀ - cancrinite and microsommite whose a-dimension is twice that of cancrinite (but with the same c-dimension) can be considered as having different ordering in adjacent channels. However, superstructure data are not yet available for these minerals.
These new minerals should all be considered as "NC - cancrinite" as this term is necessary and sufficient to describe cancrinites. The value of N should be given on the basis of the multiple subcell observed.
Keywords: Geology; Geology